2014
DOI: 10.1108/ijchm-05-2013-0225
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the direct and indirect effects of CSR on organizational commitment

Abstract: Purpose – The purpose of this study is to investigate the effect of perceived corporate social responsibility (CSR) on employees’ affective commitment through the mediating role of perceived corporate culture. Design/methodology/approach – Data were collected by means of self-administered survey. A total of 379 complete responses were obtained from tourism and hospitality organizations in China. The proposed relationships were tested usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(31 citation statements)
references
References 72 publications
3
26
0
2
Order By: Relevance
“…It is essential to engage both employees and customers in order to co-create meaningful sustainability experiences (Zhang et al, 2012), remembering that both stakeholder groups are motivated by self-interest (Wong & Gao, 2014). Guests, however, are rarely engaged in the design of CSR strategies (Moscardo & Hughes, 2018).…”
Section: Consumers: Marketing and Communicationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is essential to engage both employees and customers in order to co-create meaningful sustainability experiences (Zhang et al, 2012), remembering that both stakeholder groups are motivated by self-interest (Wong & Gao, 2014). Guests, however, are rarely engaged in the design of CSR strategies (Moscardo & Hughes, 2018).…”
Section: Consumers: Marketing and Communicationmentioning
confidence: 99%
“…While customers expect to receive a benefit for themselves from engaging in CSR activities (Wong & Gao, 2014), they are also sceptical about environmental claims for which they recognise an ulterior motive of the hotel, affecting their intention to support the hotel's CSR programme and to revisit the establishment (Rahman, Park, & Chi, 2015). Corporate values impact the consumer's engagement, as well as consumer expectations of different business models: CSR has a positive synergistic effect with service quality for full service airlines and a negative effect for low cost airlines (Seo, Moon, & Lee, 2015).…”
Section: Consumers: Marketing and Communicationmentioning
confidence: 99%
“…In fact, in treatment department of Social Security Organization of Yazd Corporate Social Responsibility had an impact on employee commitment to the organization. In research by Mortazavi et al (2010), Arndt et al (2015), Anthony and Hong (2014), Peterson (2004), Lee, Seo, and Sharma (2013), this hypothesis has been approved. H 6 : CSR adjusts the effect of CSR on QWL.…”
Section: Internal Model (Structural Model)mentioning
confidence: 97%
“…A pool of research focused on the positive associations between organizational CSR and employee attitudes [51][52][53][54]. Several studies have also shown that consumers have positive evaluations for companies demonstrating CSR activities [55,56].…”
Section: Organisational Csr and Internal Stakeholdersmentioning
confidence: 99%